2017
DOI: 10.1021/acs.energyfuels.7b02885
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Upgrading of Fine Lignite in Pulsed Fluidized Bed. 1. Experimental Study on Lignite Drying Characteristics and Kinetics

Abstract: The pulsating flow was introduced into the gas–solid fluidized bed to enhance the diffusion and stratification of lignite particles and avoid channeling and short circuits with an attempt to achieve a better drying effect for fine lignite. A pulsed fluidized bed system was established, targeting the analysis of the drying and segregation characteristics of fine lignite. With the thermal input characterized by inlet temperature, thermal energy was transported into the fluidized bed and lignite particles, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…23,24 Putra and Ajiwiguna (2017) investigated the relative influence of temperature and air velocity on drying process and concluded that the drying effect at high air velocity (1.6−2.8 m/s) is more significant than that of temperature. 23 An analogical result was also achieved by Sheng et al (2018). In the temperature range of 40−60 °C and air velocity range of 2−6 m/s, the increase of air velocity accelerates the drying of water more significantly than that of temperature, according to the work of Chandramohan (2018).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…23,24 Putra and Ajiwiguna (2017) investigated the relative influence of temperature and air velocity on drying process and concluded that the drying effect at high air velocity (1.6−2.8 m/s) is more significant than that of temperature. 23 An analogical result was also achieved by Sheng et al (2018). In the temperature range of 40−60 °C and air velocity range of 2−6 m/s, the increase of air velocity accelerates the drying of water more significantly than that of temperature, according to the work of Chandramohan (2018).…”
Section: Resultsmentioning
confidence: 76%
“…Then, the metamodel is evaluated at multiple sample points to determine model parameters by minimizing the error in the model. , The sample experiment points were determined based on an orthogonal experimental design, where four variables, namely, inlet temperature, pulsating frequency, air velocity, and bed height were analyzed. These variables were reported to have a significant effect on the segregation standard deviation of ash contents (σ ash ). , We implemented the RSM and designed the orthogonal experiments to optimize the operation conditions for drying and simultaneously separating lignite particles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With extensive exploitation, high-quality coal (HQC) reserves have been rapidly decreasing, and the development and utilization of low-quality coal (LQC) has attracted much attention. , Lignite is a typical LQC, with proven reserves of approximately 400 billion tons globally, accounting for approximately 45% of the total coal reserves. , In China, the proven reserves of lignite are approximately 13 billion tons, accounting for 13% of the total reserves . Therefore, reasonable development and utilization of lignite can alleviate the shortage of coal resources to a certain extent and make the transformation from traditional energy to renewable energy more stable.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In China, the proven reserves of lignite are approximately 13 billion tons, accounting for 13% of the total reserves. 5 Therefore, reasonable development and utilization of lignite can alleviate the shortage of coal resources to a certain extent and make the transformation from traditional energy to renewable energy more stable.…”
Section: Introductionmentioning
confidence: 99%